Creating and Implementing a Didactic Sequence as an Educational Strategy for Foreign Language Teaching - Soler Pardo, Betlem; Villacañas de Castro, Luis Sebastián; Pich Ponce, Eva (Íkala, Revista de Lenguaje y Cultura, 2014)
This text focuses on a didactic sequence (DS) which was put into practice during the school year 2011–2012 with 6th grade students from the public school Jaume I ’’El Conqueridor’’ of Catarroja (Valencia) in the area of Teaching English as a Foreign Language (TEFL). The DS was applied to the teaching of an expository text, and different pedagogic strategies—vocabulary redundancy, familiarity with the ideas involved, and a checklist to encourage student autonomy—were implemented to allow students to experiment this practice as a coherent, cohesive process adapted to their needs. The final DS design stroke a balance between a grammatical and a purely ideational focus and, as a result, students were able to improve their acquaintance with, and use of, the main features of expository writing without becoming estranged in the learning process.